AB0799 Alterations of body composition in scleroderma patients are associated with disease activity and physical activity but not with lung involvement. (12th June 2018) - Oreska, S.; Spiritovic, M.; Cesak, P.; Cesak, M.; Storkanova, H.; Smucrova, H.; Hermankova, B.; Ruzikova, O.; Mann, H.; Pavelka, K.; Senolt, L.; Vencovsky, J.; et al.
Abstract : Background: Systemic sclerosis (SSc) is characterised by fibrosis of the skin and visceral organs, especially digestive tract, and musculoskeletal and lung involvement, which limit mobility/self-sufficiency of patients and can have a negative impact on body composition and physical activity. Objectives: To assess body composition and physical activity of SSc patients and healthy controls (HC). Methods: 59 patients with SSc [50 females; mean age 52.5; disease duration 6.7 years; limited cutaneous (lcSSc, 34)/diffuse cutaneous (dcSSc, 25)] and 59 age-/sex-matched HC (50 females, mean age 52.5) without rheumatic diseases were included. SSc patients fulfilled ACR/EULAR 2013 criteria. Anthropometric parameters and body composition were assessed (by densitometry: iDXA Lunar, and by bioelectric impedance: BIA-2000-M), and physical activity was evaluated using Human Activity Profile (HAP) questionnaire. Routine biochemistry analysis was performed after 8 hours of fasting. Pulmonary function and diffusing capacity of lung were examined, disease activity was evaluated by ESSG activity index. Data are presented as mean ±SD. Results: Compared to HC, patients with SSc had significantly lower body-mass index (BMI:27.9±8.3 vs. 22.4±4.3 kg/m 2, p<0.0001) and body fat% assessed by both iDXA (BF%:38.0±7.6 vs. 32.6%±8.2%, p<0.0001) and BIA (BF%:31.3±7.6 vs. 24.3%±7.9%, p<0.0001), and decreased visceral fat weight (1.0±0.8 vs. 0.5±0.5 kg, p=0.001). Compared to HC, SSc patients also demonstrated significantly decreased lean body mass assessed by both iDXA (LBM:51.9±8.4 vs. 47.8±7.0 kg, p=0.005) and BIA (LBM:45.4±7.3 vs. 40.9±6.8 kg, p=0.005), significantly lower bone mineral density (BMD:1.2±0.1 vs. 1.0±0.1 g/cm 2, p<0.0001), and had increased extracellular mass/body cell mass (ECM/BCM) ratio (1.03±0.1 vs. 1.28±0.4, p<0.0001), which reflects deteriorated nutritional status and worse muscle predispositions for physical exercise, aerobic fitness/performance. Increased ECM/BCM in SSc patients positively correlated with disease activity (ESSG:r=0.273, p=0.0439), skin score (mRSS:r=0.371, p=0.0045) and inflammation (CRP:r=0.292, p=0.0278; ESR:r=0.302, p=0.0226). Increased ECM/BCM was also associated with worse quality of life (HAQ:r=0.438, p=0.0007; SHAQ:r=0.268, p=0.0436), fatigue (FSS:r=0.366, p=0.0040), and worse ability to perform physical activity (HAP:r=−0.644, p<0.0001). Disease activity (ESSG) negatively correlated with BF% by iDXA (r=−0.324, p=0.0138). Physical activity (HAP) positively correlated with BMD (r=0.280, p=0.032). There was no significant correlation of lung involvement with alterations of body composition. Conclusions: Compared to healthy age-/sex-matched individuals we found significant negative changes in body composition of our SSc patients, which are associated with their disease activity and physical activity, and could reflect their nutritional status, and gastrointestinal and musculoskeletal involvement. We found no significant association between lung involvement and changes of body composition. Acknowledgements: Supported by AZV-16–33574A and SVV-260373 Disclosure of Interest: None declared